Peran pengetahuan dan institutional trust dalam menggunakan layanan Digital Onboarding pada Bank Syariah di Indonesia - Sigit Kusdiyanti; Aidha Trisanty (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2026)
The ongoing digital transformation in the banking industry has encouraged Islamic banks to introduce Digital Onboarding as a faster and more convenient alternative for account opening. Despite its potential benefits, the utilization of this service remains relatively limited, highlighting the need to better understand the factors shaping public acceptance of Digital Onboarding. This study investigates the formation of customers' attitudes and intentions to use Digital Onboarding services in Indonesian Islamic banks by examining the roles of knowledge and institutional trust. A quantitative survey was conducted using structured questionnaires administered to 163 respondents who met the criteria as prospective users of digital Islamic banking services. The relationships among the proposed constructs were examined using SmartPLS based on the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. The empirical results indicate that knowledge and institutional trust contribute positively to customers' attitudes toward Digital Onboarding, with attitude subsequently strengthening their intention to use the service. In addition, knowledge and institutional trust were found to exert direct positive effects on adoption intention. These findings suggest that improving public literacy regarding Digital Onboarding, together with strengthening trust in Islamic banking institutions, represents complementary strategies for promoting the digital banking services. This study contributes to the development of digital transformation strategies for Islamic banks and enriches the literature on the adoption of digital financial services.